Sosialisasi Pengembangan Ide Usaha, UMKM & Digital Marketing bagi Pelaku Usaha di Dusun Sabrang - Mohammad ‘Ulyan; Muhammad Rizki Mashuda; Erista Dina Indriyani; Gustaf Alifian Haq (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Sabrang Hamlet in Purwosari Village has significant potential for SME development, especially in bamboo crafts. This community service activity aims to provide insights and skills to SME actors in developing businesses through product innovation and digital marketing strategies. The implementation method was conducted through face-to-face counseling and technical guidance assisted by Untidar KKN students. The activity was held on January 19, 2025, at the Purwosari Village KKN Team Post with a total of 27 participants. The activity results showed three main SMEs with development spirit: 'Happy Snack', 'Snack Teteh', and 'Box of Story'. The KKN team provided assistance in the form of logo creation, business registration, creating Google Maps locations, and digital marketing optimization through social media platforms such as TikTok Shop, Facebook, and Instagram.